Retinitis pigmentosa-linked mutations impair the snRNA unwinding activity of SNRNP200 and reduce pre-mRNA binding of PRPF8 - Zimmann, Felix; McNicoll, Francois; Thakur, Prasoon Kumar; Blažíková, Michaela; Kubovčiak, Jan; Hernández Cañás, María Clara; Nováková, Zora; Bařinka, Cyril; Kolář, Michal; Staněk, David; Müller-McNicoll, Michaela; Cvačková, Zuzana (Cellular and molecular life sciences, 2025)
Retinitis pigmentosa (RP) is a hereditary disorder caused by mutations in more than 70 different genes including those that encode proteins important for pre-mRNA splicing. Most RP-associated mutations in splicing factors reduce either their expression, stability or incorporation into functional splicing complexes. However, we have previously shown that two RP mutations in PRPF8 (F2314L and Y2334N) and two in SNRNP200 (S1087L and R1090L) behaved differently, and it was still unclear how these mutations affect the functions of both proteins. To investigate this in the context of functional spliceosomes, we used iCLIP in HeLa and retinal pigment epithelial (RPE) cells. We found that both mutations in the RNA helicase SNRNP200 change its interaction with U4 and U6 snRNAs. The significantly broader binding profile of mutated SNRNP200 within the U4 region upstream of the U4/U6 stem I strongly suggests that its activity to unwind snRNAs is impaired. This was confirmed by FRAP measurements and helicase activity assays comparing mutant and WT protein. The RP variants of PRPF8 did not affect snRNAs, but showed a reduced binding to pre-mRNAs, which resulted in the slower splicing of introns and altered expression of hundreds of genes in RPE cells. This suggests that changes in the expression and splicing of specific genes are the main driver of retinal degeneration in PRPF8-linked RP.
Keywords: Protein Binding; sestřih RNA; RNA Splicing; mutace; ribonukleoproteiny malé jaderné; RNA malá jaderná; RNA, Small Nuclear; PRPF8; SNRNP200; sestřihové faktory; RNA Splicing Factors; Retinitis pigmentosa; retinální pigmentový epitel; prekurzory RNA; Ribonucleoproteins, Small Nuclear; HeLa buňky; malý jaderný ribonukleoprotein U4-U6; vazba proteinů; RNA Precursors; lidé; HeLa Cells; Humans; Retinitis Pigmentosa; RNA-Binding Proteins; Ribonucleoprotein, U4-U6 Small Nuclear; iCLIP; Pre-mRNA splicing; Mutation; Retinal Pigment Epithelium; proteiny vázající RNA; retinopathia pigmentosa